Effect of proximate magnetic field and high permeability material on the input impedance, resonant frequency, and impedance bandwidth of some monopole antenna structures - Tibayan, Paul Bryan S. (2006)
In this study, the effects of high magnetic permeability material loading on four monopole antenna structures (straight, meandered, helix, and squiggle) of constant height are observed. Various materials of different magnetic permeabilities are utilized and their effects on the resonant frequency, input impedance, and impedance bandwidth of the antennas are studied. The effects of varying magnetic field on the material-loaded antenna are also observed with the use of an iron core solenoid. The 4NEC2 antenna simulator is used for the antenna designs and the HP 8753B network analyzer is used for the actual measurements.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Monopole antennas; Magnetic permeability; Antenna simulator; 4NEC2 antenna simulator; HP 8753B network analyzer